Training on the Development of Agro-Tourism Educational Tour Packages in Sugihen Village, Juhar District, Karo Regency, North Sumatra - Mega Hernawati Harefa; Tina Linda; Lidia Berliana Siboro; Jimmy Kelana (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
This community service program aims to develop an integrated agro-tourism and wellness educational tour package in Sugihen Village, Juhar District, Karo Regency, North Sumatra. Despite its diverse agricultural potential such as premium rice, lemongrass oil for wellness, and innovative liquid smoke technology for pest control and security the village lacks standard hospitality and structured tour operations. To bridge this gap, a team of lecturers from the Hospitality Management Study Program at Institut Bisnis IT&B Medan conducted a participatory mentoring program on May 15, 2026. The training targeted 20–25 participants from local farmer groups, family welfare empowerment (PKK) groups, youth groups, and village officials. It covered essential competencies, including hospitality mindset, tour guiding with storytelling, local mixology for welcome drinks, and standard wellness presentation using local lemongrass oil. The program successfully transformed the community's paradigm into a professional hospitality mindset and produced a customized Standard Operating Procedure (SOP) handbook for village guest management. Evaluation data showed that 100% of participants rated the instructors, modules, and their own post-training comprehension as excellent, establishing a sustainable framework for economic self-sufficiency.